Phylogenetic Patterns of Sexual Size Dimorphism in Turtles and Their Implications for Rensch’s Rule (2013)
ABSTRACT: Sexual size dimorphism (SSD) is widespread in nature and may result from selection operating differentially on males and females. Rensch’s rule, the increase of SSD with body size in male-biased-SSD species (or decrease in female-biased-SSD species), is documented in invertebrates and vertebrates. In turtles, evidence for Rensch’s rule is inconclusive and thus the forces underlying body size evolution remain obscure. Using a phylogenetic approach on 138 turtle species from 9 families, we found that turtles overall and three families follow Rensch’s rule, five families display isometry of SSD with body size, while Podocnemididae potentially follows a pattern opposite to Rensch’s rule. Furthermore, male size evolves at faster rates than female size. Female-biased-SSD appears ancestral in turtles while male-biased-SSD evolved in every polytypic family at least once. Body size follows an Ornstein–Uhlenbeck evolutionary model in both sexes and SSD types, ruling out drift as a driving process. We explored whether habitat type or sex determination might be general drivers of turtle body size evolution using a phylogenetic context. We found that males are proportionally larger in terrestrial habitats and smaller in more aquatic habitats, while the sex-determining mechanism had no influence on body size evolution. Together, our data indicate that Rensch’s rule is not ubiquitous across vertebrates, but rather is prevalent in some lineages and not driven by a single force. Instead, our findings are consistent with the hypotheses that fecundity-selection might operate on females and ecological-selection on males; and that SSD and sex-determining mechanism evolve independently in these long-lived vertebrates.